Influence of Employer Brand Image on Employee Identity - Shaker, Fahim; Ahmed, A.S. Nooruddin (Global Disclosure of Economics and Business, 2014)
This study aims to provide a framework of understanding the relation between employee identity construction and organization’s employer brand image.  Theoretically, employer brand image and identity construction are two different topics in different disciplines and have evolved separately from each others. The current paper tries to draw a relation between these two topics by addressing research work from employer branding, employee identity construction, literature on the dirty work and so forth.  Drawing this relation is significantly important as in the future it may serve the framework of understanding about certain employee’s positive or negative identity construction influenced by organization’s positive or negative employer brand image. The arguments provided here are typically based on various scholars’ findings relying on classic and contemporary text within organization theory, sociology and marketing. The paper suggests few empirical investigations as future scope of research to provide a concrete understanding of the relation between employee identity negotiation and organization’s employer brand image.JEL Classification Code: M 10; M 12; M 14